Analysis of the Pidgin Language on Dat Stick by Rich Brian - Shoufi Nisma Dewi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Pidgin dialects are at risk for vanishing because of the impact of urbanization, globalization, and the strength of significant world dialects. The shift in language, migration, and the disappearance of traditional cultural practices all make it even more challenging to preserve and maintain pidgin languages. It is necessary to acknowledge the preservation of linguistic diversity, including pidgin languages, which are important for intergroup communication and represent distinct cultural identities. The examination philosophy utilized in this study includes a blend of information assortment from "Dat Stick by Rich Brian" and a thorough survey of pertinent writing. To research the job and use of pidgin language in a melody, a subjective methodology is taken on. The pidgin-indicated word is gathered using the Data Gathering Method using a table. There should be a few guidelines for the pidgin-language category of words. It must be the result of no less than two social cooperation and doesn't contain a codification meaning. The primary method that is being utilized in this research is a literature review. determining whether or not it can be found in any dictionary. The writer takes a qualitative approach and considers the social and linguistic aspects, using definitions from a number of experts. The essayist began this subjective investigation with an interest in the intricate interaction between language and music. It was especially fascinated by the meaning of pidgin language in social articulation in the tune "Dat Stick by Rich Brian." It is motivated by this curiosity to discover and decipher the presence of pidgin language in a specific song.